'An open secret': Public housing and downward raiding in Rio de Janeiro. (October 2021) - Garmany, Jeff; Burdick, John
This article examines a case of urban displacement currently underway in central Rio de Janeiro, Brazil. In some respects, this case represents a classic example of what researchers call 'downward raiding': a type of urban displacement whereby low-income housing is exploited by higher-income groups. Yet, in other respects, it also raises important questions about the ways urban displacement happens in public housing, as well as how downward raiding operates on the ground in cities. By exploring these questions, this article aims to accomplish two goals: first, to investigate an overlooked and often hidden form of urban displacement that, in this case, coincides with a large-scale, public–private housing initiative; and, second, to critically interrogate the concept of downward raiding in order to better understand and define the process. It is argued that by placing greater emphasis on how, empirically speaking, urban displacement happens, researchers may gain new insight into diverse forms of urban displacement in cities around the world.